2022
DOI: 10.1002/rth2.12781
|View full text |Cite
|
Sign up to set email alerts
|

Pegcetacoplan in paroxysmal nocturnal hemoglobinuria: A systematic review on efficacy and safety

Abstract: Introduction: Pegcetacoplan, a pegylated penta-decapeptide, targets complement C3 to control both intravascular and extravascular hemolysis. This systematic review aims to study the efficacy and safety of pegcetacoplan in paroxysmal nocturnal hemoglobinuria (PNH). Methods:We performed a comprehensive and systematic literature search for all studies on PubMed, Google Scholar, Cochrane Library, and clini caltr ials.gov. The studies were searched using keywords "paroxysmal nocturnal hemoglobinuria" or "PNH," "Peg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…While several systematic reviews have been conducted previously on complement inhibitors for PNH treatment, [16][17][18] they have focused on individual substances or provided a descriptive review of results from clinical trials. No systematic reviews, including those of ravulizumab, have been conducted.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While several systematic reviews have been conducted previously on complement inhibitors for PNH treatment, [16][17][18] they have focused on individual substances or provided a descriptive review of results from clinical trials. No systematic reviews, including those of ravulizumab, have been conducted.…”
Section: Limitationsmentioning
confidence: 99%
“…While pivotal randomized clinical trials (RCTs) have been conducted to obtain regulatory approval for complement inhibitors, their sample sizes are relatively small, and the comparative efficacy data are restricted to a 26-week randomization period. [11][12][13][14][15] Although several systematic reviews on specific complement inhibitors exist, [16][17][18] a comprehensive analysis of short-and long-term efficacy data for all available treatments using unified criteria is still lacking. Considering that clinical trials of rare diseases have limited sample sizes, a comprehensive approach is required to establish optimal treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Pegcetacoplan is a pegylated pentadecapeptide approved in the US for the treatment of adults with PNH and in the EU for adults with PNH and anemia despite receiving C5-targeted therapy for ≥ 3 months [ 5 – 7 ]. Pegcetacoplan binds to complement component C3 and its activation fragment C3b, thereby regulating downstream effectors of complement activation [ 8 ]. In the phase 3 PEGASUS trial (NCT03500549), pegcetacoplan was found to be superior to eculizumab in improving clinical and hematologic outcomes in patients with PNH previously treated with eculizumab and had a favorable safety profile with up to 48 weeks of treatment [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%